PELAYANAN KESEHATAN REPRODUKSI REMAJA DI ACEH TIMUR DITINJAU PERSPEKTIF HUKUM DAN ETIKA - Dewi Suryati; Irsyam Risdawati; Marice Simarmata (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Adolescents' lack of knowledge about reproductive health, as well as lack of access to adolescent-friendly health services, are an important background in this study. This study aims to analyze the implementation of reproductive health services for adolescents in East Aceh from a legal and ethical perspective, and assess the extent to which the principle of protection of adolescent health rights is carried out in accordance with local regulations and religious norms. This study uses a qualitative method with a juridical-sociological approach. Data was obtained through interviews with health workers, adolescents, religious leaders, and regional policy makers, as well as documentation of health service regulations and ethical guidelines. Data analysis was carried out in an analytical descriptive manner by considering positive legal norms and medical ethical principles. The results of the study show that although there is a national regulation guaranteeing the right to reproductive health of adolescents, its implementation in East Aceh faces various obstacles, such as cultural resistance, limited trained medical personnel, and lack of public understanding of the urgency of reproductive health education. From a legal perspective, there is a gap between national policy and local qanun, while ethically, health services still often clash with the conservative values of local communities. In conclusion, adolescent reproductive health services in East Aceh still need to be improved through an interdisciplinary approach that harmonizes aspects of national law, local values, and principles of medical ethics. Keywords: Reproductive Health, Adolescents, Legal Ethics. Abstrak: Adolescents' lack of knowledge about reproductive health, as well as lack of access to adolescent-friendly health services, are an important background in this study. This study aims to analyze the implementation of reproductive health services for adolescents in East Aceh from a legal and ethical perspective, and assess the extent to which the principle of protection of adolescent health rights is carried out in accordance with local regulations and religious norms. This study uses a qualitative method with a juridical-sociological approach. Data was obtained through interviews with health workers, adolescents, religious leaders, and regional policy makers, as well as documentation of health service regulations and ethical guidelines. Data analysis was carried out in an analytical descriptive manner by considering positive legal norms and medical ethical principles. The results of the study show that although there is a national regulation guaranteeing the right to reproductive health of adolescents, its implementation in East Aceh faces various obstacles, such as cultural resistance, limited trained medical personnel, and lack of public understanding of the urgency of reproductive health education. From a legal perspective, there is a gap between national policy and local qanun, while ethically, health services still often clash with the conservative values of local communities. In conclusion, adolescent reproductive health services in East Aceh still need to be improved through an interdisciplinary approach that harmonizes aspects of national law, local values, and principles of medical ethics. Keywords: Reproductive Health, Adolescents, Legal Ethics.